2015
DOI: 10.3923/jp.2015.127.141
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Bubaline Isolate of Cryptosporidium Species from Egypt

Abstract: Cryptosporidium an apicomplexan parasite has the ability to induce diarrhea in bovines, goats, pigs, dogs and cats worldwide. In this study, buffalo calves fecal samples were examined after staining their smears with Modified Ziehl-Neelsen Stain (MZN). Ileal sections were examined for the detection of pathological changes. Further molecular characterization was done using nested PCR amplification and partial sequence analysis. The detected oocysts were morphologically similar to Cryptosporidium parvum. Light m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
3
1
0
Order By: Relevance
“…This agreed with previous findings that the interval which covered the natural Cryptosporidium oocyst shedding period in mice was about 24 days (Matsui et al 2001) or about 3-4 weeks (Lacroix et al 2001). Also, in this study, C. parvum oocysts detected in mice fecal smears were morphologically similar to those of C. parvum described in previous studies (Hassanain et al 2011;Abdelrahman et al 2015). In this study, a gradual reduction in oocyst shedding was noticed in all infected animal groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This agreed with previous findings that the interval which covered the natural Cryptosporidium oocyst shedding period in mice was about 24 days (Matsui et al 2001) or about 3-4 weeks (Lacroix et al 2001). Also, in this study, C. parvum oocysts detected in mice fecal smears were morphologically similar to those of C. parvum described in previous studies (Hassanain et al 2011;Abdelrahman et al 2015). In this study, a gradual reduction in oocyst shedding was noticed in all infected animal groups.…”
Section: Discussionsupporting
confidence: 93%
“…Light microscopic examination of C. parvum-infected ileal sections revealed the presence of altered mucosal architecture, with sloughing and complete erosion of epithelial cells, shortening, blunting, stunting and atrophy of the intestinal villi. These findings agreed with Abu El Ezz et al 2011and Abdelrahman et al (2015). Sasahara et al (2003) found that at the time when the number of C. parvum oocysts in the ileum was maximal, absorptive and columnar goblet cells decreased in the ileal epithelium with a significant reduction in the height of the villi.…”
Section: Discussionsupporting
confidence: 88%
“…2 (2020) THERAPEUTIC EFFICACY OF GINGER (Zingiberofficinale), GINSENG (Panax ginseng) … of histopathological corrections. These results agreed with Abu El Ezz et al [12], Abdelrahman et al [43] and Abouel-Nour et al [44]. In this study, the intestinal villi of infected ginger, ginseng high dose treated mice groups showed more histologic repair and normal tissue appearance in comparison to control and other treated groups.…”
Section: Histopathological Examinationsupporting
confidence: 92%
“…This result should be attributed to the immunodeficient situation that flared up the infection. This was evident research [46], and another study [47] found a higher number of developmental stages in the epithelial cells of the infected control group's gut [47,48]. A reduction in the villus to crypt ratio in mice infected with C. parvum oocysts was observed by some studies.…”
Section: Discussionmentioning
confidence: 66%